Bahasa Inggris - Ramdansyah Fitrah; Saparuddin Siregar; Sugianto Sugianto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The goal of this study is to use the Islamic Social Reporting (ISR) Index to determine social responsibility disclosure at Gayo Islamic Rural Bank (BPRS Gayo). Including items such as investment and financial indicators, products, services, or labor employees, as well as social, environmental, and organizational governance, which is thought to be utilized as a beginning point in Islamic CSR disclosure criteria. Gayo Islamic Rural Bank is the subject of this study, which is based on the annual report for 2020. Content analysis is a method for analyzing data. According to the findings, the Gayo Islamic Rural Bank's social responsibility disclosure level with the ISR Index was 42.6 percent. That means that social responsibility exposure at Gayo Islamic Rural Bank was still limited or could only meet 42 of the maximum score if Gayo Islamic Rural Bank exposure on the ISR Index was completely disclosed.